KEDUDUKAN SAKSI MAHKOTA DALAM PEMBUKTIAN TINDAK PIDANA PEMBUNUHAN BERENCANA (Studi Putusan Nomor 46/Pid/2014/PT-Mdn) - Intan Lestari Harita (Jurnal Panah Hukum, 2022)
The existence of a crown witness is never explicitly stated in the Criminal Procedure Code, but in practice this crown witness is often presented by the Public Prosecutor as witness evidence due to a lack of evidence. The use of this crown witness is still a debate in Indonesia until now because there is no legal certainty. The problem in this thesis is how is the position of the crown witness in proving the crime of premeditated murder (Decision Study Number: 46/Pid/2014/PT-Mdn). The type of research used by the author is normative research using the statutory approach method and the case approach method. Data collection in this study was carried out by taking an inventory of all primary legal materials, secondary legal materials and tertiary legal materials. The data obtained were processed and analyzed qualitatively. Based on the results of research and discussion on the position of the crown witness in proving the crime of premeditated murder (Study of Decision Number: 46/Pid/2014/PT-Mdn). Is that the crown witness is the main witness or key witness who comes from or is taken from a suspect or other accused who jointly commits a crime. This crown witness is not explicitly regulated in the Criminal Procedure Code but the crown witness is explicitly recognized in Jurisprudence No. 1986 K/Pid/1989 dated March 21, 1990, Supreme Court Decision No. 2437/K/Pid.Sus/2011 and Circular Letter of the Attorney General of the Republic of Indonesia No. B-69/E/02/1997 Year 1997. And the validity of this crown witness should be recognized in the Criminal Procedure Code and the government together with the DPR as the legislators should make a law regarding crown witnesses